2015
DOI: 10.1371/journal.pone.0123508
|View full text |Cite|
|
Sign up to set email alerts
|

Chinese Herbal Therapy and Western Drug Use, Belief and Adherence for Hypertension Management in the Rural Areas of Heilongjiang Province, China

Abstract: BackgroundTraditional Chinese medicine (TCM) including Chinese herbal therapy has been widely practiced in China. However, little is known about Chinese herbal therapy use for hypertension management, which is one of the most prevalent chronic conditions in China. Thus we described Chinese herbal therapy and western drug users, beliefs, hypertension knowledge, and Chinese herbal and western drug adherence and determinants of Chinese herbal therapy use among patients with hypertension in rural areas of Heilongj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
0
7
0
1
Order By: Relevance
“…Both showed that those who took traditional medications were non-adherent to their antihypertensive medication regimen. 26 , 27 The possible reasons were the belief that traditional medications must not be taken together with prescribed antihypertensives and lack of awareness about the danger of uncontrolled hypertension. 25 The concern about western drug side effects and the belief that traditional CAM has fewer negative side effects may also contribute towards the higher level of non-adherence to antihypertensives among CAM users.…”
Section: Discussionmentioning
confidence: 99%
“…Both showed that those who took traditional medications were non-adherent to their antihypertensive medication regimen. 26 , 27 The possible reasons were the belief that traditional medications must not be taken together with prescribed antihypertensives and lack of awareness about the danger of uncontrolled hypertension. 25 The concern about western drug side effects and the belief that traditional CAM has fewer negative side effects may also contribute towards the higher level of non-adherence to antihypertensives among CAM users.…”
Section: Discussionmentioning
confidence: 99%
“…The knowledge of TCM is of paramount importance for the choices of patients when they are selecting medical assistance (Wardle et al 2011 ). Li et al ( 2015 ) argued that patients with high education levels are more likely to use TCM. This claim is in agreement with the study conducted by Shumer et al ( 2016 ) in Japan.…”
Section: Results: Findings and Discussionmentioning
confidence: 99%
“…Unlike other studies that included participants of various socioeconomic levels, most of our study participants were low-income, undereducated farmers. The low educational level of our participants might be responsible for their lack of knowledge about risky behaviors, such as high salt intake and smoking, and their poor adherence to antihypertensive medication owing to poor understanding of the instructions given by health care providers 25 ) . Overall poverty and seasonal income fluctuation might have also made it difficult to regularly access good quality health services.…”
Section: Discussionmentioning
confidence: 99%